Review effectiveness of indigenous local microorganisms in degrading hexavalent chromium (Cr(VI)) in Batik liquid waste - Reza Fauzi Dwisandi; Frista Mutiara; Elsa Nurfauziah; Vita Meylani (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
The batik industry in Indonesia has an IKM (Small and Medium Industry) scale so that it does not yet have adequate waste treatment. In the long term, waste is disposed of directly into the environment which can damage aquatic ecosystems and harm human health. Textile wastewater has a complementary picture and has a deep color. One of the most dangerous heavy metals contained in textile waste is hexavalent chromium (Cr(VI)). Several ways can be done to reduce hexavalent chromium (Cr(VI)) by bioremediation. Based on the results of the literature review, it shows that the bioremediation agents from single isolate microorganisms that are most effective in degrading chromium with high efficiency are Bacillus subtilis and Pseudomonas aeruginosa. The most effective consortium servers with constant reduction rates are the consortium of bacteria genus Mesophilobacter, Methylococcus, Agrobacterium, Neisseria, Xanthobacter, Deinococcus, Sporosarcina, and Bacillus by reducing BOD levels by 85.71%. The hexavalent chromium-degrading microorganisms are characterized by the presence of chromate reductase enzymes, mostly gram-negative bacteria, and a high growth rate.